Usability of Geographic Information: current challenges and future directions - Brown, Michael; Sharples, Sarah; Harding, Jenny; Parker, C.J.; Bearman, N.; Maguire, M.; Forrest, D.; Haklay, M.; Jackson, M. (Elsevier, 2013)
The use of Geographic Information or GI, has grown rapidly in recent years. Previous research has identified the importance of usability and user centred design in enabling the proliferation and exploitation of GI. However, the design and development of usable GI is not simply a matter of applying the tried and tested usability methods that have been developed for software and web design. Dealing with data and specifically GI brings with it a number of issues that change the way usability and user centred design can be applied. This paper describes the outcomes of a workshop held in March 2010 exploring the core issues relating to GI usability. The workshop brought together an international group of twenty experts in both human factors and GI, from a wide range of academic and industrial backgrounds. These experts considered three key issues, the stakeholders in GI, key challenges applying usability to GI and the usability methods that can be successfully applied to GI. The result of this workshop was to identify some areas for future research, such as the production of meaningful metadata and the implications of blurring of the line between data producers and data consumers.